Gamificación y aprendizaje asistido por la IA para el área del lenguaje en los niños/as de 3 años. - Tituaña Quinaluiza, Viviana Mercedes (2025)
This project addresses the topic of gamification and AI-assisted learning in such a way that it is possible to promote the language area in 3-year-old boys and girls since they are in the initial stages of schooling; they require strengthening this ability that, although innate, can be improved by applying innovative tools to promote it. The main objective was to identify gamification and AI-assisted learning strategies to offer tools that help improve early childhood education in language in three-year-old children in Ecuador by applying the observation technique and surveys. The methodology was based on a mixed approach with a non-experimental, descriptive design. The techniques applied were the survey with its respective instruments, the questionnaire, and observation, with its observation record. The sample was made up of 15 parents. As a result, it was found that most parents think that learning through AI and gamification improves language development in three-year-old boys and girls. Thus, it is concluded that there is a relationship between gamification and AI and the improvement of the language of 3-year-old boys and girls.